Planejamento e síntese de novos candidatos a protótipos de fármacos anti-HIV, desenhados a partir da delavirdina, um inibidor não nucleosídico da transcriptase reversa - Machado, Antônio Silva (2015)
AIDS is considered an epidemic disease shaping up as a serious public health problem. Since its discovery in 1981, considerable efforts have been made to better understand the HIV infection mechanism thus, propelling the research and drug development process. According to their mechanism of action, HIV drugs can be classified into six mainly subgroups: nucleoside reverse transcriptase inhibitors (NRTIs), protease inhibitors (PI), non-nucleoside reverse transcriptase inhibitors (NNRTIs), nucleotide reverse transcriptase inhibitors (NtRTI ), entry inhibitors and integrase inhibitors. Currently, searching for safer and more effective drugs showing less collateral effects remains an encouraging pace. In this context, our work describes a synthesis of a new family of heterocyclic compounds, chemically related to delavirdine, a NNRTIs currently used in AIDS treatment. Bioisosterism strategy was applied to obtain synthetic products (54a-54h) in four steps only. Conventional heating method (A) and optimized microwave reactor (B) methodology were both compared by means of their intermediate products yields. Results showed increased yields of partial products (20a-20h [91-98%]); (29a-29h [69-88%]); (37a-37h [82-92%]) for microwave reactor methodology, as well a gain in the time spent during the procedure. All compounds (20a-20h; 29a-29h; 37a-37h e 54a-54h) were characterized by Nuclear Magnetic Resonance of Hydrogen (1H NMR), Carbon (13 C NMR) and Infrared spectroscopy (IR).